L’article comme exposant de l’aspect ? La valeur aspectuelle du SN et la valeur aspectuelle d’une collocation verbo-nominale - Muryn, Teresa (Studia Romanica Posnaniensia, 2015)
The definition of aspect as a semantic category enables aspectual analysis of the NP to be carried out. Noun phrases are viewed as aspectually equivalent to VPs. In both cases, the analyses are likely to be conducted along the same set of principles of aspectual decomposition. The point is to ascertain whether and how the category of aspect may contribute to the contrastive description of articles between a language with no articles and an article-language.